(untitled) (El Taco en la Brea, 2019)
Developments in the episode of the encounter between Odysseus and Nausicaa, narrated from the sixth canto of the Odyssey, when the hero finally reaches the island of the Phaeacians, are in the essay discussed mainly based on the occurrence of crying. Weeping disarms the bellicose impetus and facilitates the integration of those who give themselves to the groups of which they are part or host them. In a second moment, the re-creation of the same episode, in James Joyce’s Ulysses, is focused, emphasizing the inevitable contrasts, summarized in the exchange of the solidarity lament accentuated by Homer for the egoistic, or romantic, pursuit of pleasure and success.